Comisarenco Mirkin, D. (2017). Eclipse de siete lunas. Mujeres muralistas en México. Artes de México. 264 pp. - Gómez Murillo, Ana Guillermina (Letras Históricas E-ISSN: 2448-8372, 2019)
Reseña de libro.